PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 010 SIALANG MAKMUR KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Jamil, Muhammad; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The study was carried on because of the low grade science students learning outcomes SD Negeri 010 Sialang Makmur Kecamatan Kelayang Kabupaten Indragiri Hulu which has not reached the KKM (Minimum completeness criteria) set is 70. The problem of this research is "Does the application of cooperative learning model think Pair Share (TPS) can Improve Learning Outcomes science Student Class V SD Negeri 010 Sialang Makmur Kecamatan Kelayang Kabupaten Indragiri Hulu? ". The purpose of this study is to improve learning outcomes fifth grade science students at SD Negeri 010 Sialang Makmur Kecamatan Kelayang Kabupaten Indragiri Hulu to implement cooperative learning model Think Pair Share (TPS). The hypothesis of this study is If implemented cooperative learning model Think Pair Share (TPS), it can improve learning outcomes fifth grade science students SD Negeri 010 Sialang Makmur Kecamatan Kelayang Kabupaten Indragiri Hulu. This research was done in class V SDN 010 Sialang Makmur in the 2nd half the Academic Year 2015-2016 at the time the study began on April 6, 2016 until April 25, 2016. This research is a classroom action research (PTK) is conducted in two cycles. Subjects of this study were students of class V SD Negeri 010 Sialang Makmur Kecamatan Kelayang Kabupaten Indragiri Hulu beehive with the number of students 16 people, 10 men and 6 women. Based on the results of the research activity sheet teacher, student activity sheets and student learning outcomes are seen rising on each cycle. In the first cycle of teacher activity with an average percentage of 72.91% persiklus increased to 91.66% in the second cycle. Activities of students in the first cycle of the first with an average percentage of 70.83% persiklus increased to 87.49% in the second cycle. Increase student learning outcomes of basic score is the percentage of completeness 37.5%, with an average of 63.75, an increase in the first cycle with the percentage of completeness of 62.5% with an average of 70.31 and a percentage increase of 9.33%. Increased again in the second cycle is the percentage of completeness of 87.5% with an average of 78.12 and a percentage increase of 18.39%. So the results of this study in accordance with the hypothesis of action.                                  Keywords: cooperative learning, Think Pair Share, IPA Learning Outcomes